The Role of Anecdotal Humor in Indonesian Stand-Up Comedy: A Study of "Lapor Pak" - Fadillah Fauziah Putri; Jovan Morientes Nigel Manihuruk; Meisya Audreyanna Azzahra; Putri Pratiwi; Yosi Evelyn Tondang (Jurnal Intelek Insan Cendikia, 2024)
This study explores the role of anecdotal humor in Indonesian stand-up comedy, with a focus on the YouTube talk show Lapor Pak. Using qualitative analysis, the research examines how comedians employ relatable anecdotes to address contemporary social issues, crafting engaging and humorous stories that connect with viewers. The study highlights the key elements of anecdotal text including Abstract, Orientation, Crisis, Reaction, and Coda, and illustrates how these components are applied in Lapor Pak to convey messages and critique societal norms. The findings underscore the importance of stand-up comedy as a tool for social commentary and cultural reflection, showcasing the comedians' ability to create witty reactions that propel the comedic narrative. This research enhances the understanding of stand-up comedy as a powerful medium for both education and social critique in Indonesian culture